The controversy between Sedano and Iriarte: tip and root of the spine - Pedro Ruiz Pérez (Philologia Hispalensis, 2019)
López de Sedano opened his Parnaso español with Espinel’s translation of horatian “Arte poética”. Criticism by Iriarte in 1777, as a preamble to his own version of the epistle, gave rise to a series of answers and rejoinders until 1785, with the response in volume VII of the Parnaso and Iriarte’s “joco-serious dialogue” Donde las dan las toman. The controversy moves from the features of translation to the design and production of Sedano’s anthology. The analysis of the final answer in the Colloquios de la espina reveals the aesthetic differences between the two authors, representing two opposing positions in the conception of good taste and the ways to update it. The evaluation of the rules and the poetry of the seventeenth century are two of the central points of the discrepancy.